Mezuniyet oncesi Adli Tıp Eğitimi Almış Oğrencilere Yonelik Bir Anket Calışması - Salaçin, Serpil; Çekin, Necmi; Özdemir, Mehmet Hakan; Kalkan, Şemsi (The Bulletin of Legal Medicine, 1997)
Because the number of forensic medicine specialist is insufficient, most of the first examination of the legal cases are under the responsibility of general practitioners, in Turkey. Present circumstances lead to discrepancies between the standards of the courts. It is obvious that achieving the acceptable number for forensic medicine specialist needs much more time and forensic medicine lectures for medical undergraduates is very important in our country. The training and experience requirements for the medical undergraduates should be configurated by considering the circumstances of Turkey. This study was planned to evaluate the opinion of the 5th and 6th years medical undergraduates for their forensic medicine training program. It has been conducted by questionnaires. The study group was composed of 202 students. The results showed that 178 (88.1 %) of the students were satisfied during three weeks of full time attendance to the program. Individual student practices could not be performed especially on crime scene investigation, autopsy and evaluation of morphological findings. Therefore more than half of the students found themselves inadequate in performing above subjects. Ill (55 %) students offered to have more practice hours as well as active individual involvement. Most of the students also mentioned that they need much more involvement in practical activities.Key words: Forensic medicine, teaching medical undergraduates, medical students, curriculum, Turkey.
Keywords: forensic medicine; teaching medical undergraduates; medical students; curriculum; Turkey